APPLICATION OF AGILITY ASSESSMENT MODEL (AAM) IN ASSESSING AGILITY DEGREE IN THE TECH ECOSYSTEM (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study  examines  the security of cloud computing management infrastructures from  the perspective of the insider attacker. It is also proposed to design and implement a security system for the infrastructures  responsible for  the  management  of  cloud  computing  environment  against  the  insider attacker. To achieve this aim, we designed a security solution that handles login verification and login information  storage.  The  application  stores  the  login  information  of  every personnel  who  has  been defined to access the system. The solution also stores information about infrastructure managers, the host server,  the  virtual  server,  the  smart  routers  and  switches,  all  of  which  are  used for  storage  and transmission of data over the internet. The infrastructural security solution is applicable to Infrastructure as a service (IaaS). The system is also capable of handling authentication of cloud members, verification and monitoring of data transfer, thus maintaining network security for our cloud environment and data confidentiality. The security system also provides the administrator with the privilege of monitoring who is  logged into the cloud environment,  in  other to protect the network from  hackers. Because design method  is  required  to  complete  this  research,  Waterfall  Design  Methodology  was  adopted for  the research, design and implementation methodology. Programming  is performed using PHP, coding  is done using HTML platform, Couchbase offline server is used as our local server for hosting this cloud network security system, and advanced network security Standard algorithm is implemented for ensuring security framework.